Урожайність гібридів соняшнику залежно від густоти стояння рослин в Степу України - Кунєв, Дмитро Володимирович; Kuniev, Dmytro (ЦНТУ, 2023)
В даній випускній кваліфікаційній роботі вивчено вплив густоти стояння рослин на урожайність різних гібридів соняшнику. Мета досліджень – Дослідити вплив густоти стояння рослин на урожайність гібридів соняшнику при вирощуванні їх в умовах Степу України. Встановлено, що найбільшу урожайність соняшнику, було отримано при вирощуванні гібриду N4H471CL з густотою стояння рослин 55 тис./га. Abstract: In this final qualification work, the influence of plant stand density on the yield of various sunflower hybrids was studied. The purpose of the research is to study the influence of plant stand density on the yield of sunflower hybrids when grown in the conditions of the Steppe of Ukraine. It was established that the highest yield of sunflower was obtained when growing the N4H471CL hybrid with a plant density of 55 thousand/ha.
Productivity of sunflower hybrids depending on plant density in the Steppe of Ukraine
Keywords: гібриди соняшнику; густота рослин; урожайність; якісні показники; sunflower hybrids; plant density; productivity; quality indicators